K2Ti6O13 Nanoparticle-Loaded Porous rGO Crumples for Supercapacitors - Lee, Chongmin; Kim, Sun Kyung; Chang, Hankwon; Jang, Hee Dong (Nano-Micro Letters, 2019)
One-dimensional alkali metal titanates containing potassium, sodium, and lithium are of great concern owing to their high ion mobility and high specific surface area. When those titanates are combined with conductive materials such as graphene, carbon nanotube, and carbon nanofiber, they are able to be employed as efficient electrode materials for supercapacitors. Potassium hexa-titanate (K2Ti6O13, KTO), in particular, has shown superior electrochemical properties compared to other alkali metal titanates because of their large lattice parameters induced by the large radius of potassium ions. Here, we present porous rGO crumples (PGC) decorated with KTO nanoparticles (NPs) for application to supercapacitors. The KTO NP/PGC composites were synthesized by aerosol spray pyrolysis and post-heat treatment. KTO NPs less than 10 nm in diameter were loaded onto PGCs ranging from 3 to 5 µm. Enhanced porous structure of the composites was obtained by the activation of rGO by adding an excessive amount of KOH to the composites. The KTO NP/PGC composite electrodes fabricated at the GO/KOH/TiO2 ratio of 1:3:0.25 showed the highest performance (275 F g−1) in capacitance with different KOH concentrations and cycling stability (83%) after 2000 cycles at a current density of 1 A g−1. Highlights 1 K2Ti6O13 nanoparticle (KTO NP)-loaded porous reduced graphene oxide crumples (PGCs) were fabricated. 2 The specific capacitance was improved due to the synergy effect between KTO and PGC. 3 The KTO NP/PGC composites can be promising electrode materials for supercapacitors.